The Role of Phonology in Language Learning: A Case Study of Indonesian EFL Learners - Luthfi, Jihan; Melani, Melani; Zira, Nazwa Kaila; Lubis, Yani (MUDABBIR Journal Research and Education Studies, 2025)
Phonology plays a crucial role in second language acquisition, particularly in enhancing pronunciation, listening comprehension, and overall communicative competence. This study explores the role of phonology in English language learning among Indonesian EFL (English as a Foreign Language) students. Using a qualitative descriptive approach, data were collected through semi-structured interviews with twelve university students majoring in English Education. Findings reveal that learners often struggle with English sounds that do not exist in their first language, such as /?/ in think, which impacts pronunciation and listening. Although phonological instruction was limited, students expressed a strong belief in its importance and advocated for more explicit teaching of sound systems. The study suggests the integration of phonology-focused strategies in EFL curricula to support learners’ oral proficiency.